Pengaruh Media Pembelajaran Poster terhadap Kemampuan Menulis Aksara Sunda Kelas VII di SMP Santa Lusia - Megawati Megawati; Opah Ropiah (Universitas Cokroaminoto Palopo, 2026)
The urgency of this research is to determine the effectiveness of posters as a learning media in improving the ability of seventh-grade students to write Sundanese script. The preservation of Sundanese script as part of local cultural heritage requires effective instructional strategies, as many junior high school students still experience difficulties in writing Sundanese characters accurately and systematically. This study aims to examine the effect of poster-based learning media on the Sundanese script writing ability of seventh-grade students at SMP Santa Lusia. The research employed a quantitative pre-experimental method using a one-group pretest–posttest design. The population consisted of all Grade VII students at SMP Santa Lusia, and the sample was Class VII-A comprising 30 students, selected through simple random sampling. The sampling criteria included active enrollment in Grade VII and participation in the complete learning process during the study. Data were collected through observation, written tests (pretest and posttest), and documentation. The research instrument was an essay-based writing test that had undergone validity testing. Data analysis techniques included validity testing, normality testing using the Shapiro–Wilk test, and hypothesis testing using a paired samples t-test. The results showed that the mean pretest score was 64.7 (minimum 20; maximum 94), while the mean posttest score increased to 85.2 (minimum 70; maximum 100). The Shapiro–Wilk test indicated that the data were normally distributed (Sig. > 0.05). The paired samples t-test revealed a significance value of 0.000 (Sig. 2-tailed < 0.05), indicating a statistically significant difference between pretest and posttest scores. Therefore, poster-based learning media significantly improve students’ ability to write Sundanese script.